Advertising and integrated brand promotion - O'Guinn, Thomas C.; Allen, Chris T.; Semenik, Richard J. (Mason, USA : South-Western Cengage Learning, 2009)
Public relations focuses on communication that can foster good will between a firm and constituent groups such as customers, stockholders, employees ,government entitles, and the general public.
Includes index.
Keywords: Advertising Research; Media and Support Organizations; Integrated Brand Promotion